Assortative mating and female labor supply - Christian Bredemeier; Falko Juessen (Institute for the Study of Labor (IZA), 2010)
This paper investigates the pattern of wives' hours disaggregated by the husband's wage decile. In the US, this pattern has changed from downward-sloping to hump-shaped. We show that this development can be explained within a standard household model of labor supply when taking into account trends in assortative mating. We develop a model in which assortative mating determines the wage ratios within individual couples and thus the efficient time allocation of spouses. The economy-wide pattern of wives' hours by the husband's wage is downward-sloping for low degrees, hump-shaped for medium degrees, and upward-sloping for high degrees of assortative mating. A quantitative analysis of our model suggests that changes in the gender wage gap are responsible for the overall increase in hours worked by wives. By contrast, the fact that wives married to high-wage men experienced the most pronounced increase is a result of trends in assortative mating.
urn:nbn:de:101:1-201010132736
Keywords: E24; J22; J16; D13; 330; female labor supply; assortative mating; gender wage gap